Role and regulation of phosphatidylinositol 3-kinase ß in platelet integrin α2ß1 signaling - Consonni, A.; Cipolla, L.; Guidetti, G.; Canobbio, I.; Ciraolo, E.; Hirsch, E.; Falasca, Marco; Okigaki, M.; Balduini, C.; Torti, M. (2012)
Integrin α2β1–mediated adhesion of human platelets to monomeric type I collagen or to the GFOGER peptide caused a time-dependent activation of PI3K and Akt phosphorylation. This process was abrogated by pharmacologic inhibition of PI3Kβ, but not of PI3Kγ or PI3Kα. Moreover, Akt phosphorylation was undetectable in murine platelets expressing a kinase-dead mutant of PI3Kβ (PI3KβKD), but occurred normally in PI3KγKD platelets. Integrin α2β1 failed to stimulate PI3Kβ in platelets from phospholipase Cγ2 (PLCγ2)–knockout mice, and we found that intracellular Ca2+ linked PLCγ2 to PI3Kβ activation. Integrin α2β1 also caused a time-dependent stimulation of the focal kinase Pyk2 downstream of PLCγ2 and intracellular Ca2+. Whereas activation of Pyk2 occurred normally in PI3KβKD platelets, stimulation of PI3Kβ was strongly reduced in Pyk2-knockout mice. Neither Pyk2 nor PI3Kβ was required for α2β1–mediated adhesion and spreading. However, activation of Rap1b and inside-out stimulation of integrin αIIbβ3 were reduced after inhibition of PI3Kβ and were significantly impaired in Pyk2-deficient platelets. Finally, both PI3Kβ and Pyk2 significantly contributed to thrombus formation under flow. These results demonstrate that Pyk2 regulates PI3Kβ downstream of integrin α2β1, and document a novel role for Pyk2 and PI3Kβ in integrin α2β1 promoted inside-out activation of integrin αIIbβ3 and thrombus formation.